A physical model for dual gate a-InGaZnO thin film transistors based on multiple trapping and release mechanism. (April 2019) - Li, Linan; Ba, Wenqiang; Wang, Wei; Li, Ling; Xu, Guangwei; Wang, Lingfei; Ji, Zhuoyu; Lu, Congyan; Banerjee, Writam
Abstract: In this paper, we present a physical model for dual gate amorphous InGaZnO (a-IGZO) thin film transistors (TFTs) based on multiple trapping and release mechanism. Calculation results of I–V characteristic based on this model are in good agreement with the experimental data. Based on the proposed model, we also analyze the inner physical properties of dual gate a-IGZO TFTs, such as electric potential and carrier concentration. Highlights: A physical model for dual gate amorphous InGaZnO (a-IGZO) thin film transistors (TFTs) based on multiple trapping and release mechanism is proposed. Calculation results of I-V characteristic based on this model are in good agreement with the experimental data. Based on the proposed model, we also analyze the inner physical properties of dual gate a-IGZO TFTs, such as electric potential and carrier concentration.